2019
DOI: 10.5114/jcb.2019.91226
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular brachytherapy for extensive right-heart and pulmonary artery sarcoma – a case report

Abstract: Primary sarcoma of the heart is a rare but devastating tumor. Median survival with conventional treatment is 8-12 months. When resection is not feasible, patients often succumb to heart failure secondary to obstruction of blood flow, valve dysfunction, chamber compression or conduction abnormalities. Palliative treatment options include systemic chemotherapy and external beam irradiation. We herein describe a novel technique using endovascular brachytherapy, aiming at reducing tumor mass, alleviating right ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Through a backward citation search, 24 additional articles were retrieved, bringing the total to 74 articles included in this study. Figure 1 shows the preferred reporting items for systematic reviews and meta-analyses (PRISMA) flowchart and screening methods, while Table 1 displays the general characteristics of the patient population [18–85] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through a backward citation search, 24 additional articles were retrieved, bringing the total to 74 articles included in this study. Figure 1 shows the preferred reporting items for systematic reviews and meta-analyses (PRISMA) flowchart and screening methods, while Table 1 displays the general characteristics of the patient population [18–85] .…”
Section: Resultsmentioning
confidence: 99%
“…In our review, we found that local spread was common, involving the atrial wall, myocardium, and pulmonary veins. The lungs were identified as the most common site of metastasis; however, some authors demonstrated a widespread pattern of metastasis involving multiple organs [26,46,71] . Metastasis was confirmed by biopsy for most authors or inferred from staging images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IS shows various histological subtypes of differentiation, such as fibrosarcoma, leiomyosarcoma, anaplastic sarcoma, osteosarcoma, and chondrosarcoma [5]. The standard therapy currently available for IS is only surgical resection, as no systemic treatment has been established for this rare disease [2, 6, 7].…”
Section: Introductionmentioning
confidence: 99%